Future information communication technology and applications : ICFICE 2013 - Kim, Jung Tae; Sahama, Tony; Yang, Chung-Huang; Jung, Hoe-Kyung (Lecture Notes in Electrical Engineering, 2013)
These proceedings are based on the 2013 International Conference on Future Information & Communication Engineering (ICFICE 2013), which will be held at Shenyang in China from June 24-26, 2013. The conference is open to all over the world, and participation from Asia-Pacific region is particularly encouraged. The focus of this conference is on all technical aspects of electronics, information, and communications ICFICE-13 will provide an opportunity for academic and industry professionals to discuss the latest issues and progress in the area of FICE. In addition, the conference will publish high quality papers which are closely related to the various theories and practical applications in FICE. Furthermore, we expect that the conference and its publications will be a trigger for further related research and technology improvements in this important subject.  "This work was supported by the NIPA (National IT Industry Promotion Agency) of Korea Grant funded by the Korean Government (Ministry of Science, ICT & Future Planning). "